2022
DOI: 10.1371/journal.pone.0277033
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and gene co-expression network analyses of high-risk beef cattle defines immunological mechanisms and biological complexes involved in bovine respiratory disease and weight gain

Abstract: Bovine respiratory disease (BRD), the leading disease complex in beef cattle production systems, remains highly elusive regarding diagnostics and disease prediction. Previous research has employed cellular and molecular techniques to describe hematological and gene expression variation that coincides with BRD development. Here, we utilized weighted gene co-expression network analysis (WGCNA) to leverage total gene expression patterns from cattle at arrival and generate hematological and clinical trait associat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Our objective in this study was to identify differences in gene expression and associated host-driven biological systems that may be impacted by marketing decisions and how these influence eventual BRD morbidity after backgrounding arrival, in order to explore potential mechanisms of BRD development or resistance that may be leveraged in future studies. While both our research group and others have used the blood RNA-Seq methodology to identify potential predictive markers and mechanisms related to BRD [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], this study, to our knowledge, is one of the first to utilize said technologies to evaluate how marketing decisions, with relationship to BRD, influence inflammatory- and immune-mediated mechanisms in cattle. Importantly, exposure to an auction market setting and an order-buyer facility for only three days was associated with the differential expression of 2961 genes representing 113 biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Our objective in this study was to identify differences in gene expression and associated host-driven biological systems that may be impacted by marketing decisions and how these influence eventual BRD morbidity after backgrounding arrival, in order to explore potential mechanisms of BRD development or resistance that may be leveraged in future studies. While both our research group and others have used the blood RNA-Seq methodology to identify potential predictive markers and mechanisms related to BRD [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], this study, to our knowledge, is one of the first to utilize said technologies to evaluate how marketing decisions, with relationship to BRD, influence inflammatory- and immune-mediated mechanisms in cattle. Importantly, exposure to an auction market setting and an order-buyer facility for only three days was associated with the differential expression of 2961 genes representing 113 biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Trials utilizing tissue samples such as lung, lymph nodes, and tonsils have demonstrated how each viral and bacterial agent acts as a pathogen, causing clinical disease ( 11 , 12 ). More recently, the whole blood transcriptome has been investigated for potential predictive molecules, protective immunological mechanisms, and regulatory patterns of BRD in beef cattle ( 13 , 14 , 36 , 37 ). Whole genome sequencing has also been used to examine bacterial transcriptome profiles and identify ARGs and the drug classifications of which species have developed resistance ( 10 , 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%